Checklist of the Quill mites (Acariformes: Syringophilidae) of the World - Glowska, Eliza; Chrzanowski, Mateusz; Kaszewska, Katarzyna (Zootaxa, 2015)
Mites of the family Syringophilidae (Acariformes: Cheyletoidea) are ectoparasites inhabiting the quills of various feather types in many groups of birds. Until now, 334 valid species and 60 genera of quill mites have been described and recorded from 482 bird species (95 families and 24 orders). Currently, the family is divided into 2 subfamilies: Syringophilinae Lavoipierre, 1953 with 260 species grouped in 49 genera, and Picobinae Johnston and Kethley, 1973 with 74 species grouped in 11 genera. Mites of the subfamily Syringophilinae inhabit quills of primaries, secondaries, tertials, rectrices and wing coverts and just occasionally the body feathers; representatives of the subfamily Picobinae live predominantly inside the body feathers. The rapid increase of the knowledge on biodiversity and systematics of quill mites started in end of the 1990s; numerous new descriptions appeared since that time and taxonomic rearrangements make an urgent need to summarize all previous data. We present a complete checklist of the family Syringophilidae of the world including the following data: a species name, author(s), references, a number of first page of description, figure numbers in descriptions, depository of type and non-type materials, host spectrum and geographical distribution. The checklist is additionally provided with the table including bird hosts and associated quill mite species.